Endovascular treatment of cerebral dural arteriovenous fistulas with SQUID 12. Issue 5 (October 2020) - Lozupone, Emilio; Bracco, Sandra; Trombatore, Pietro; Milonia, Luca; D'Argento, Francesco; Alexandre, Andrea; Valente, Iacopo; Semeraro, Vittorio; Cioni, Samuele; Pedicelli, Alessandro
Background: Endovascular therapy with liquid embolic agents (LEAs) is the gold standard for the treatment of cerebral dural arteriovenous fistulas (cDAVFs). The aim of the study is to retrospectively evaluate effectiveness, safety, and midterm follow-up results of endovascular treatment of cDAVFs using SQUID 12. Methods: Between June 2017 and January 2020 the authors retrospectively reviewed clinical, demographic and embolization data of 19 consecutive patients with cDAVF who underwent embolization using SQUID 12. The number of arteries catheterized for each procedure, the total amount of embolic agent, the occlusion rate, the injection time, any technical and/or clinical complications were recorded. Mid-term follow-up with DSA was reviewed. Results: 20 procedures were performed in 19 patients. A transarterial approach was accomplished in 19 procedure; a combined transvenous-transarterial approach was realized in 1 treatment. The average time of injection was 33 minutes (2–82 minutes), and the average amount of SQUID 12 was 2.8 mL (0.5–6 mL). Complete angiographic cure at the end of the procedure was achieved in 17 patients. No major periprocedural adverse events were recorded. Mid-term follow-up was achieved in 15 out of 19 patients and confirmed complete occlusion of the cDAVFs in 13/15 patients (87%); in 2 of the initially cured patients a small relapse was detected. Conclusions: The treatment of the cDAVFs using SQUID 12 was effective and safe. The lower viscosity seems to allow an easier penetration of the agent with a high rate of complete occlusion of the cDAVFs.